The various controls on the platform architecture of carbonate buildups in the Central Luconia Province, Offshore Sarawak - Yusliandi, A. (Slovnaft VURUP a.s, 2019)
Cenozoic isolated carbonate buildups around the world have been studied by many authors. These buildups are commonly dominated by corals, coralline algae, and large benthic foraminifera. Their development is the result of the interaction of multiple factors including tectonics (subsidence and antecedent topography), eustasy, climate, siliciclastic influx, nutrition, and environmental condition, which control the relationship between carbonate production and accommodation space, and furthermore determine the internal sedimentary architecture and facies distribution withi n carbonate buildups. In this study, controlling factors that influence the platform architecture of buildups in Central Luconia will be discussed. Factors will be differentiated based on local influence on single buildup, or if they have a regional effect on the entire Central Luconia region. Based on the quantitative description of the predictive attributes, there are similarities and differences that indicate the controlling factors not only affect regionally but there also factors that work uniquely on single buildup. Â© 2019